ANALISA KEBIJAKAN PENGANGKATAN SEKRETARIS DESA (SEKDES) MENJADI PEGAWAI NEGERI SIPIL (PNS) DI KABUPATEN DEMAK - Fina Sinarita; Kushandajani .; Supratiwi . (Journal of Politic and Government Studies, 2013)
The purpose of this study was to determine the appointment of Secretary of Rural Policy Implementation (Sekdes) become civil servants (PNS) in the year 2007 to 2012 in Demak. In analyzes using 4 indicators George C. Edward III is communication, resources,Jurnal Ilmu Pemerintahan, Volume , No. , Tahun 2013, Hal:Online di http://fisip.undip.ac.iddisposition and bureaucratic structures. The results showed that the implementation of policy in the appointment of a civil servant Sekdes Demak has been successful, although in practice there are constraints on the Sekdes who reject this policy because they are earning so crooked revenues will decrease drastically after appointed as civil servants and civil service retirement if prior to 65 years after PNS to 56 years so that the losses of 9 years. As well as gaps and sense of discrimination for the village of Kadesh and other devices that are in the minus because they are not earning so crooked they are jealous and want to be appointed civil servants to be more prosperous. Find solutions for local government in Demak Sekdes want to be a civil servant appointed by Regulation No. 3 of 2010 is about 50% additional income from former crooked garapannya cashed and given every month, so it does not lose too big Sekdes.Keywords: Public Policy, Secretary of the village and civil servants.